Effects of Dry Needling in patients having Lateral Epicondylitis (Central Medical College Journal, 2025)
Background: Lateral epicondylitis (LE) commonly known as tennis elbow, is a degenerative condition affecting the myotendinous junction of the wrist extensors at the lateral epicondyle, predominantly causing pain and reduced function in the affected arm. It is commonly seen in individuals over 45 years old who engage in high-risk activities involving repetitive wrist extension. Conservative management is the mainstay of treatment, but dry needling (DN) is a newer technique with limited evidence in treating LE. Methods: This study involved patients diagnosed with lateral epicondylitis at a tertiary care hospital in Bangladesh. Participants were divided into two groups: one receiving dry needling combined with conservative management, and the other receiving conservative management alone. Pain and functional outcomes were measured using the Patient-Rated Tennis Elbow Evaluation (PRTEE) and the Visual Analog Scale (VAS) at baseline, 1 month, and 3 months post-treatment. Results: A total of 60 patients with lateral epicondylitis were enrolled and randomized into two groups: Group A (n=30) received dry needling in addition to conservative management (oral acetaminophen, exercises, and elbow counterforce brace), while Group B (n=30) received conservative management only. After accounting for losses to follow-up, 28 patients in Group A and 27 in Group B completed the 3-month follow-up. Baseline demographic and clinical characteristics were comparable between the groups (p>0.05). At 1 and 3 months, Group A showed significantly greater improvements in PRTEE pain, functional, and total scores compared to Group B (p